A phenomenology of place identity for Wonder Valley, California: homesteads, dystopics, and utopics - Sowers, Jacob Richard (Kansas State University, 2010)
Sprawling over 180 square miles of California’s Mojave Desert, Wonder Valley was founded in the early 1950s and today is an unincorporated community of approximately 1,000 residents. The community’s landscape is expansive and unsettling, featuring a chaotic assortment of residences that include abandoned homesteads, squatter settlements, artists’ studios, middle-class cabins, and luxury vacation properties. This dissertation explores Wonder Valley’s enigmatic place identity from residents’ point of view, drawing on an experiential understanding of place grounded in humanistic and phenomenological geography. Specifically, the dissertation makes use of Edward Relph’s explication of place identity to guide empirical inquiry and conceptual structure. Drawing on resident interviews, place observations, and textual analysis, the dissertation identifies and explicates three distinct Wonder Valley identities—homesteaders, dystopics, and utopics. Arriving in the 1950s, homesteaders were Wonder Valley’s first inhabitants and express a practical connection to the landscape that is interpreted in terms of environmental reach, specifically, the creation, maintenance, and extension of environmental and place order. During the 1970s, as many homesteaders abandoned Wonder Valley, dystopics arrived and today include two subgroups: first, a criminal element pulled to Wonder Valley because of its local isolation but regional proximity to Los Angeles; and, second, destitute squatters pushed out from other communities and having nowhere else to go. The third group identified is utopics, primarily artists from Los Angeles and San Francisco, who arrived in the early 1990s, attracted by Wonder Valley’s natural beauty and sacred ambience. The dissertation explores how these three groups arrived at different times, for different reasons, to create vastly different landscapes, to engage in opposing aims and activities, and to understand Wonder Valley’s meaning as a place in greatly contrasting ways. These differences in meaning are most directly expressed in the common areas of public land, which have often become sites of inter-group tension and conflict, particularly in regard to abandoned homesteads and the use of off-road vehicles. To interpret this group conflict conceptually, the dissertation develops what is termed existential ecotone— a unique mode of place experience generated by overlapping but contrasting modes of being-in-place.
Keywords: Place Identity; ecotone; phenomenology; desert; California; Geography (0366)